On the efficiency of cash settlement - Charles M. Kahn; William Roberds (Federal Reserve Bank of Atlanta, 1995)
This paper investigates the question of why banks almost always settle payments in cash as opposed to debt. Our model suggests that adverse selection with respect to the quality of bank assets may be the primary motivation underlying this practice. Banks with higher-quality assets prefer not to exchange debt with other banks if their debt is indistinguishable from that of banks with lower-quality assets. Banks with higher-quality assets prefer to sell off assets to informed outside agents in return for cash, which can then be used in settlement. Willingness to settle in cash serves as a signal of the quality of a bank's assets; hence, in equilibrium all banks settle in cash. If information flows are disrupted so that no outsiders are informed, then the signaling value of cash settlement is lost. The last result is consistent with the use of debt-based settlement schemes during the National Banking Era (1864-1914).
Keywords: 330; Banks and banking - History; Money